PENGARUH KOMPOSISI SUBSTRAT DAN DOSIS INOKULUM LARU TERHADAP NILAI GIZI AMPAS SAGU (Metroxylon sp) FERMENTASI* - Triani Adelina (Jurnal Peternakan, 2008)
Sago waste is by product of sago processing. Sago production in Bengkalis District is 368.420,2 tons/year, and sago waste production is assumed approximately 147.368,08 tons/year. Nutrients composition of sago waste are 11.68% of water, 3.38% of crude protein, 1.01 % of crude fat, 12.44% of crude fiber and 12.43% of ash. Nutrients contents especially crude protein could be increased by biological processing such as fermentation. Fermentation pursued to increase the nutrient contents, microbial growth and flavor. In this process, sago waste mixed with rice brand to increase the nutrient contents and microbial growth. The objectives of this experiment were to establish effects of substrates composition and laru inoculum doses on nutrients contents of sago waste fermentation. Treatments were consisted of 2 factors in a Completely Randomized Design (CRD). Treatments were: A: substrates (A) ; A1 == 100% sago waste A2 == 90% sago waste+10% rice brand; A3 = 80% sago waste+20% rice brand and B : inoculums (B); B1 =3 g/kg substrate; B2 = 5 g/kg substrate; B3 ,. 7 g/kg substrate. The results showed that 80% substrate composition of sago + 20% rice brand with 7 g/kg substrate of inoculums dosage was the best among the treatments, with the nutrient content was 10,53% ofcrude protein and 18,83% of crude fiber.